Opportunities and Fields of the Kazakhstan and Russia Integration in the Field of Crisis Response - V. Dodonov (Евразийская интеграция: экономика, право, политика, 2019)
The article deals with the possibilities and promising areas of cooperation between Russia and Kazakhstan, as well as multilateral cooperation of the Common Economic Space in the neutralization of the crisis caused by external shocks. It highlights the main directions of the global crisis negative impact on the economy of Kazakhstan and Russia, on the basis of which mechanisms and tools to neutralize this effect are offered, with emphasis on those that can be most effective as part of the integration of the CES.